The influence of financial literacy on the personal financial management of government employees - Rahayu, Caecilia Wahyu Estining; Rahmawati, Christina Heti Tri (Faculty of Economics and Business Mulawarman University, 2019)
Financial literacy is a combination of financial knowledge, financial attitude and financial behavior that every individual needs in order to avoid financial issues. By performing personal financial management appropriately, a person can improve the quality of his life. This research aims at examining the effects of financial knowledge, financial attitude and financial behavior on the personal financial management of government employees in Kalibawang Community Health Center. The population of this research is every active government employee in Kalibawang Community Health Center and the sample is 50 of them. This research uses a questionnaire and sampling method by means of a saturated sampling technique and applies Multiple Linear Regression analysis. In the results of this research, it is found that the financial attitude and financial behavior had a positive and significant effect on the personal financial management of government employees in Kalibawang Community Health Center. Otherwise, financial knowledge has a negative and insignificant effect on personal financial management. These results are expected to provide insight on the government employees in Kalibawang Community Health Center that better financial attitude and financial behavior of the government employees do influence to better their personal financial management.